Renewal of Criminal Law in Combating Corruption Crimes - Hendrio Hamid Pesik; Rahmat Dwi Putranto (JURNAL HUKUM SEHASEN, 2022)
Criminal law reform is a policy that demands reform of all aspects that touch philosophical aspects, namely changes or orientations towards principles to the stage of the values that underlie them. Therefore, the inclusion of criminal acts of corruption led to rejection from various circles. One of them is a criminal law expert and the formulator of the Draft Law on the Criminal Procedure Code, Andi Hamzah, believes that the regulation of criminal acts of corruption should be regulated separately, because it is temporary.